Anxiety-Attachment , Avoidance-Attachment and Gender as Predictors of Empathy. [article]. - Parcon, A.
From two-factor scales (o.e. affective and cognitive components), recent researches in the study of empathy showed that three factors (i.e. emotional contagion, emotional disconnection, and cognitive empathy) accounted for an integrative view of empathy (Carre, Sefaniak, Bensalah, & Richard, 2013). Given the recent developments, this study aimed to see the significant predictors for each of these empathy components. Three-hundred thirty seven participants (n=337), ages 15-24 (M=19.33, SD = 1.337) took part in the study. Regression analyses showed that females were more likely to experience emotional contagion and cognitive empathy while males were more likely to experience emotional disconnection. Further, high anxiety-attachment and low avoidance-attachment predicts emotional contagion. On the other hand, high avoidance-attachment predicts emotional disconnection, while low avoidance-attachment predicts cognitive empathy. Gender was also seen to significantly moderate the avoidance attachment in terms of their effect on emotional disconnection and cognitive empathy. Males with high avoidance attachment were more likely to emotional disconnect; while females with low avoidance were more likely to cognitive empathize. The discussion emphasized the relevance of attachment orientation in the development of empathy. Further, implications on interpersonal relations were also explored.
Keywords: Attachement; Empathy; Emotional contagion; Emotional disconnection